Factors Affecting the Emotional Labor in Food Services – The Case of Van as a Tourism Destination - Icoz, Onur; Cetin, Ibrahim; Gokdeniz, Ayhan (Turizam, 2018)
In the hospitality industry, the long-term success of any business heavily depends on the customer satisfaction, which is the center of the service provided by employees who are directly in touch with the quests in every step of the process. Moreover, it requires an effective management of employee emotions for the success of business. The basic objective of this study is to determine the major factors affecting emotional labor of employees in food and beverage industry. The study aims to explore the situational factors (influence of interaction frequency, interaction intensity, interaction variety and emotional dissonance) and demographic variables on the emotional labor consisting of two sub parts as surface acting and deep acting. As the data collection tool of survey method, a questionnaire was prepared based on the scales that have been developed by the authors from the literature. The data collected from the employees of the 30 luxury cafes and cafe restaurant in 2017 summer period, and 243 of them were found to be convenient for analysis. A set of statistical tests comprised of regression, correlation, one way anova tests and LSD were implemented in the analysis to find out the relationship among the major factors and emotional labor. Some major findings can be summarised as; emotional labor was mostly influenced by emotional dissonance and interaction variety, positive relationship was found between the interaction frequency and the intensity of interaction, emotional dissonance and interaction variety; there is a significant correlation between the dimension of intensity of interaction and gender of the employees and female workers display more intensive emotional labor when they are on duty.